"Migration and Health" in public health perspective course experience in a medical faculty, Turkey. (30th September 2020) - Aslan, D
Abstract: Introduction: Public health practices of medical training should be modifiable according to the needs of the population. Turkey has been facing with the refugee problem since 2011. In this regard, new requirements are arising for medical professionals starting from the medical faculties. In this paper, a new elective course introduced for medical students on migration and health will be defined. Materials and Methods: "Migration and Health" in Public Health Perspective Course was proposed for the first phase medical students at Hacettepe University, Faculty of Medicine. The proposal was approved by the official mechanisms of the medical faculty after a detailed assessment. The aim of the approved Course was to gain information and increase awareness on health aspect of migration based on good medical practices. Results: The Couse was held between October 2019 and January 2020 once a week for two hours. Fifteen Turkish and other international students completed the Course. Interactive training techniques were used during the Course. Feedbacks of the students were regularly taken after each class once a week. Reflections of the students were also recorded both at the beginning and at the end of the Course. The students were successful in achieving the aims of the Course. Additionally, another achievement was gained which was not proposed at the beginning of the Course. The "positive" attitude of the medical students refusing discrimination against refugees was the secondary and may be a more worthy outcome of the Course. All students were able to look at the refugee problem with good medical values and based on the basic rights of the humanity. Conclusions: The students reported their satisfaction about the Course. As the Course was applied for the first time, it is open for revision according to the feedbacks received during of the Program. The Content, the methods will be overviewed before the next year. Key messages: Medical students' curricula could have been updated due to the new and the dynamic developments in the population. Refugee issue needs a global perspective which the medical students need to learn.